Empowering Future Educators: Navigating Challenges in the Teaching Practicum for Prospective Teachers and Supervisors - Muhammad Junaid; Akash Mahamud; Golam Ali Azgar Hossain Maruf; Babatunde Temitope Joseph (Al-Qanṭara, 2024)
This study critically examines the challenges faced by prospective teachers and their supervisors during the teaching practicum, with a focus on identifying innovative solutions to improve the practicum experience. Drawing on a descriptive survey of 339 prospective teachers and 30 supervisors from three universities, the research uncovers significant challenges, including classroom management, lesson planning, resource shortages, and workload stress. An important and novel finding of this study is the gender-based divergence in these challenges: female teachers reported higher levels of workload-related stress, whereas male teachers were more concerned with classroom management and lesson planning difficulties. Supervisors faced barriers related to resource constraints, limited time for effective mentoring, and communication gaps with school personnel. In a field often dominated by generic assessments of practicum challenges, this study offers innovative insights by contextualizing the practicum experience within the socio-cultural and resource-constrained setting of Pakistan. It highlights the differential impact of gender on teaching practicum challenges, an area previously underexplored in this context. The research proposes targeted solutions, such as gender-sensitive professional development programs, optimized resource allocation, and improved communication structures between schools and universities. These findings contribute to enhancing the design of teacher education programs in developing countries, providing policymakers and educators with actionable strategies for reforming teacher training to meet the demands of modern classrooms.